EFFECTIVENESS OF WETLAND-BASED WAVE AND OPTICS MODULES ON STUDENTS' SCIENTIFIC LITERACY ABILITIES - Khairunnisa, Yasmine; Hafizah, Ellyna; Salupi, Wida (Jurnal Pendidikan Matematika dan IPA, 2024)
Wetlands that dominate the area in South Kalimantan are one of the indigenous science learning resources that can help students learn. However, the insertion of wetlands has not commonly been done on a learning media which directly used in class. The developed wetlands-based module on wave and optics aimed to enhance students"™ scientific literacy which leads to the success of learning by integrating indigenous science. It was implemented for thirty science education students by using a group pretest-posttest design. The results showed that 29 students gained increased scientific literacy during the implementation, with the improvement in each aspect of scientific literacy categorized as moderate. In addition, the Wilcoxon test result showed a significant enhancement of scientific literacy after using the wetlands-based module of wave and optics. Thus, the wetland-based module is effective in improving students"™ scientific literacy abilities.